Nickelodeon Teenage Mutant Ninja Turtles: Follow the Leader - Teitelbaum, Michael; Keast, Jennifer H. (Ashland, OH Bendon Publishing Inc., 2017)
Drive and Find! Buckle up, because its time to take a tour of Axle City with Blaze! Kids will love meeting all the Monster Machines while they zip around town searching for hidden objects in eight busy scenes, with STEM curriculum seamlessly woven throughout the book, its a supercharged challenge from beginning to end. Lets Blaaaze! -- Amazon.com.
Keywords: Ninja Turtles -- Juvenile literature; Juvenile works